INTERPRETATION OF QUR’ANIC VERSES AND HADITHS IN THE POETRY OF AHMAD YASSAWI - Nigina Umurova (International Journal of Literature and Language Studies, 2026)
The article analyzes the artistic and mystical interpretation of the verses of the Quran and hadiths in the hikmah of Ahmad Yassawi. The features of the use of verses and hadiths in the form of direct quotation, contextual interpretation, and symbolic references are highlighted. The artistic expression of the ideas of repentance, remembrance, guidance , and spiritual perfection in the work of Ahmad Yassawi in connection with the Quran and hadiths is scientifically analyzed.